Exclusion, Power, and Gender in Daniel Asorey: Toward the Utopian Dimension of the Dystopian? - Kumor, Karolina; Moszczyńska-Dürst, Katarzyna (Madrygal. Revista de Estudios Gallegos, 2024)
This article analyses Daniel Asorey’s dystopian novel As mulleres da fin do mundo (2018) in light of Hannah Arendt’s (2004) and Eleni Varikas’ (2017) theories of exclusion. According to those philosophers, figures of exclusion who emerge on the margins are not just “the outcasts of the world” (Varikas 2017), but figures who assert themselves in non-belonging and non-obedience to dominant discourses and practices. As this article demonstrates, Asorey’s novel embodies these figures and the underlying mechanisms of exclusion. As mulleres da fin do mundo is part of the dystopian boom, since it has many of the constituent elements of this genre (a degenerate world, technocratic, dictatorial structures that deny individuals the exercise of their rights, subaltern and repressed realities, etc.). At the same time, with its incentive to rebellion, the text dreams of a utopia: a (trans)matria without binarisms and discrimination based on any ground such as sex, class or race. This analysis focuses in particular on the means used by dystopias to denounce the mechanisms of exclusion operating in the capitalist and heteropatriarchal system; with the traditional family, infinite economic growth, consumerism and religion as pillars.